2019
DOI: 10.3389/fpubh.2019.00305
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Disease Risk Across the Growing Human-Non Human Primate Interface: A Review of the Evidence

Abstract: Most of the human pandemics reported to date can be classified as zoonoses. Among these, there is a long history of infectious diseases that have spread from non-human primates (NHP) to humans. For millennia, indigenous groups that depend on wildlife for their survival were exposed to the risk of NHP pathogens' transmission through animal hunting and wild meat consumption. Usually, exposure is of no consequence or is limited to mild infections. In rare situations, it can be more severe or even become a real pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
101
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 105 publications
(113 citation statements)
references
References 189 publications
0
101
0
3
Order By: Relevance
“…Finally, there is a public health concern linked to the risk of transmission to humans (324)(325)(326)(327). Dromedary camel infection by Mycobacterium tuberculosis or Mycobacterium bovis was reported in several countries (328)(329)(330)(331)(332)(333)(334)(335)(336)(337)(338)(339)(340)(341). Another mycobacterium, Mycobacterium avium subsp.…”
Section: Burnetii Still Neglected In the Oie List Of Zoonotic Pathmentioning
confidence: 99%
“…Finally, there is a public health concern linked to the risk of transmission to humans (324)(325)(326)(327). Dromedary camel infection by Mycobacterium tuberculosis or Mycobacterium bovis was reported in several countries (328)(329)(330)(331)(332)(333)(334)(335)(336)(337)(338)(339)(340)(341). Another mycobacterium, Mycobacterium avium subsp.…”
Section: Burnetii Still Neglected In the Oie List Of Zoonotic Pathmentioning
confidence: 99%
“…NHPs are increasingly implicated as potential sources of emerging zoonotic diseases in humans [ 7 , 8 ]. Indigenous groups that depend on wildlife for survival were exposed to the risk of the transmission of NHP pathogens through hunting, consumption of bushmeat [ 9 ] and through other ways; for example, by sharing non-flowing water sources, fruits and plant sources that NHPs have used. Concerning adenoviruses, virologists have long wondered about the possibility that NHP adenoviruses may one day pose a risk to humans [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The chikungunya virus is maintained in nature in both urban and sylvatic cycles involving mosquito vectors and human or vertebrate animal hosts [27]. A study indicated that the unprecedented destruction of natural barriers between nonhuman primates and humans has increased health risks for a large population, including people living in urban areas [28]. Additionally, the chikungunya virus is an RNA virus with a high mutation rate of up to one million times higher than that of their hosts, and these high rates are associated with enhanced virulence and evolvability, which are beneficial traits for viruses [29].…”
Section: Discussionmentioning
confidence: 99%